SECURITY CONSIDERATIONS FOR REMOTE ADMINISTRATION IN ELECTRONIC COMMUNICATIONS INFRASTRUCTURE - Поляков, Олександр; Кузьмін, Андрій; Івко, Сергій (SWorldJournal, 2025)
The article examines security aspects of organizing remote administration in electronic communications infrastructure. The focus is on analyzing potential threats and vulnerabilities, including traffic interception, password guessing, social engineering,